Meminimalisasi Tingkat Kehilangan Air Baku Dengan Menggunakan Sistem Dinamis di PT. AQUA - Delfitriani, Delfitriani; Wardatul Jannah, Fadia; Syarbaini, Ahmad (JURNAL AGROINDUSTRI HALAL, 2026)
AMDK is processed raw water that is safely packaged for human consumption, including mineral and demineralized water. However, there are still several issues in the provision of AMDK, with the main problem being water loss, also known as Non-Revenue Water (NRW). This study aims to identify the contributing factors to AMDK loss at PT. AQUA and to analyze and explain the dynamic system model involved. The method applied in this research is a dynamic system approach, used to design, depict, and simulate a system that changes over time. The interactions among variables in this structure are then translated into mathematical models and simulated using Powersim software to trace their developments over time. The findings of this study indicate that there are variables causing water loss, and these variables fall into three subsystems. Alternative scenarios, namely the moderate, optimistic, and pessimistic scenarios, are developed over a period of ten years to reduce water loss. By examining the results of these three scenarios, the company can implement these alternatives to minimize water rejection, thus reducing water loss and enhancing operational efficiency.